Functional Analysis of Plasmodium vivax Dihydrofolate Reductase-Thymidylate Synthase Genes through Stable Transformation of Plasmodium falciparum - Auliff, Alyson M.; Balu, Bharath; Chen, Nanhua; O’Neil, Michael T.; Cheng, Qin; Adams, John H. (PLOS ONE, 2012)
Mechanisms of drug resistance in Plasmodium vivax have been difficult to study partially because of the difficulties in culturing the parasite in vitro. This hampers monitoring drug resistance and research to develop or evaluate new drugs. There is an urgent need for a novel method to study mechanisms of P. vivax drug resistance. In this paper we report the development and application of the first Plasmodium falciparum expression system to stably express P. vivax dhfr-ts alleles. We used the piggyBac transposition system for the rapid integration of wild-type, single mutant (117N) and quadruple mutant (57L/58R/61M/117T) pvdhfr-ts alleles into the P. falciparum genome. The majority (81%) of the integrations occurred in non-coding regions of the genome; however, the levels of pvdhfr transcription driven by the P. falciparum dhfr promoter were not different between integrants of non-coding and coding regions. The integrated quadruple pvdhfr mutant allele was much less susceptible to antifolates than the wild-type and single mutant pvdhfr alleles. The resistance phenotype was stable without drug pressure. All the integrated clones were susceptible to the novel antifolate JPC-2067. Therefore, the piggyBac expression system provides a novel and important tool to investigate drug resistance mechanisms and gene functions in P. vivax.